Arental Experiences of Parent Support Groups for Children with Developmental Disabilities in the Accra and Cape Coast Metropolis, Ghana - Nyaku, S. (University of Ghana, 2024)
This study explored the experiences of parents who participate in support groups for children with developmental disabilities. Using a descriptive qualitative design guided by a phenomenological approach, eleven parents were interviewed through semi-structured discussions to understand their perspectives on the role of parent support groups. The data were analyzed thematically, revealing five major themes: caregiving experiences, coping strategies, awareness of support groups, perceived benefits, and challenges encountered. Findings showed that parent support groups provided participants with holistic education, access to useful information, and both emotional and material support. The groups also offered opportunities for psychological well-being and social connectedness. Parents emphasized that interacting with others facing similar circumstances fostered understanding, resilience, and a sense of belonging. Overall, parent support groups were found to play a vital role in enhancing the caregiving experiences and well-being of parents of children with developmental disabilities. The study highlights the importance of strengthening and expanding such groups to promote family resilience and psychological health. Implications for clinical practice and recommendations for future research are discussed.
MPhil. Clinical Psychology
Keywords: Developmental disabilities (DD); children; parents